PENDAMPINGAN POTENSI PEREMPUAN DAN PENGEMBANGAN HOME INDUSTRI MELALUI MOTEKAR(MOTIVASI KETAHANAN KELUARGA) DI KECAMATAN SUKAJADI KELURAHANKAMPUNG TENGAH PEKANBARU - Salmiah Salmiah; Yulia Novita; Alfiah Alfiah; Ristiliana Ristiliana; M.Iqbal Lubis; Rizki Fiprinita (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Refers to the law and government regulation that women in economic activities in the family systems are very important considering the family is the smallest socio-economic unit in society which is the basic foundation of all institutions. Women have an important role in the survival of the family economy through the MOTEKAR program, the existing home industry development can develop the woman's potential especially housewives. MOTEKAR is a Family Resilience Motivator from the local community in the village who have the desires, knowledge, and skills to carry out the family empowerment activities through the synergy of various related programs available in the village to improve the quality of the family life. The purpose of this dedication is to provide training about the processing of sardines, from the processing step until the sardines are ready to be marketed which can be used as a micro business in the family. This dedication conducted in Kampung Tengah district, Sukajadi Pekanbaru. The method used in this dedication is counseling. Counseling is the best way to give knowledge to the community. The result of this dedication is there are business opportunities, especially in the processing of sardines which get attention as a home industry development. Keywords: Perempuan,Home Industri, MOTEKAR,